Wideband, multiband, and smart reconfigurable antennas for modern wireless communications - Matin, Mohammad A. (IGI Global, 2016)
This book showcases current trends and novel approaches in the design and analysis of the antennas that make wireless applications possible, while also identifying unique integration opportunities for antennas and wireless applications to work together.